The 'Lack of Separation' Revisited: Small Business Owners and Risk - Susan Coleman; Richard Cohn (Journal of Entrepreneurial Finance, 2001)
The close link between the personal financial affairs of a small business owner and his or her firm has been noted in prior research. This article compares attitudes toward risk on the part of small business owners (SBOs) and non-small business owners (NSBOs). In addition, it compares the personal balance sheets of SBOs to those of NSBOs to determine if SBOs hold a higher level of risky assets. Results reveal that small business owners express a greater willingness to accept risk and hold a higher level of risky assets in their personal portfolios. This finding is consistent with small business owners' willingness to own and operate small firms which are, by their very nature, risky.
Keywords: L25; G32; M13; 650; Firm Performance; Financing Policy; Financial Risk; Risk Management; Capital Structure; Ownership Structure; New Firms; Startups